International Monetary Fund Administrative Tribunal Reports, Volume V, 2006. (International Monetary Fund, 2010)
This paper provides an analysis of the Tribunal's jurisprudence for the period is provided in an introductory chapter 'Developments in the Jurisprudence of the International Monetary Fund Administrative Tribunal: 2006.' In deciding on an application, the Tribunal shall apply the internal law of the IMF, including generally recognized principles of international administrative law concerning judicial review of administrative acts. The guidelines provide for performance assessments at prescribed intervals during the fixed term and impose obligations on both the fixed-term appointee and supervisors. The Tribunal emphasized that the provisions governing the mandatory resignation and possible subsequent reemployment of staff who serve as Advisors to Executive Directors indicate that a staff member who so resigns has no assured right to resume employment as a member of the IMF's staff. In order to assess whether an Applicant has initiated administrative review procedures on a timely basis, the Administrative Tribunal may be required to determine when the Applicant was on notice that he had been adversely affected by an administrative act of the IMF.